Evaluating Academic Service Quality at Universitas Sains Al-Qur’an Wonosobo: A SERVQUAL-Based Analysis of Student Satisfaction and Improvement Priorities - Fatmawati, Ria; Murfi, Ali (Global Educational Research Review, 2025)
Purpose –  This study examines the quality of academic services at Universitas Sains Al-Qur’an (UNSIQ) Wonosobo, focusing on student satisfaction and identifying key service gaps based on the SERVQUAL model. The study aims to provide actionable recommendations for improving service quality by analyzing the gaps between student expectations and actual service delivery. Methods/Design/Approach – A quantitative approach was adopted, using a survey distributed to 952 students across six faculties. The SERVQUAL model informed the design of the questionnaire, which measured the importance and satisfaction of academic services through a 5-point Likert scale. Importance-Performance Analysis (IPA) was applied to identify priority areas for improvement. Data validity and reliability were tested using SPSS. Findings – Significant gaps were found in UNSIQ’s academic services, particularly in the Tangibles dimension, where the largest gap (1.71) was in internet access. Other dimensions such as Reliability and Responsiveness also showed noticeable gaps. The findings indicate the urgent need for improvement in digital infrastructure to enhance student satisfaction. Originality/Value – This study adds to the literature on service quality in higher education by applying the SERVQUAL model in the context of an Indonesian university. The findings align with international studies on the importance of infrastructure and service quality in shaping student satisfaction and institutional loyalty. The study also provides actionable recommendations for UNSIQ, which can serve as a reference for similar institutions seeking to improve service quality. Practical Implications – The research suggests that UNSIQ should prioritize enhancing both physical and digital infrastructure to better meet student expectations. Implementing regular feedback mechanisms could further align services with student needs, thereby increasing satisfaction and loyalty. Keywords Academic service quality, student satisfaction, SERVQUAL, higher education, Importance-Performance Analysis (IPA) Paper type Research paper